Pengaruh Edukasi Kesehatan Reproduksi Di Era Gen Z Sebagai Upaya Peningkatan Kesadaran Remaja Di SMA Nur Adia - Huwaina Af’idah; Ade Irma; Rapotan Hasibuan; Tri Andika Putra Ginting; Ainun Jariyah; Jihan Azzahra (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Reproductive health is a crucial factor in adolescent development, particularly among Generation Z, characterized by rapid technological advancements, changing lifestyles, and increased exposure to risky behaviors. A lack of understanding of reproductive health among adolescents can lead to various physical and mental health problems, including reproductive infections, sexually transmitted infections, and mental health issues. This community service program aims to broaden adolescents' knowledge and awareness of the importance of maintaining reproductive health in the Generation Z era. The activity was held on December 6, 2025, at Nur Adia High School and involved 60 students as participants. The methods applied in this program included health education, interactive discussions, and question-andanswer sessions. The results showed an increase in participants' understanding of reproductive health, personal hygiene practices, healthy lifestyles, and prevention of risky behaviors. It is hoped that this activity can be a preventative measure in increasing awareness of reproductive health and supporting the development of a healthy and responsible young generation. Keywords: Reproductive Health, Gen Z Youth, Health Education